2010
DOI: 10.1111/j.1365-2958.2010.07469.x
|View full text |Cite
|
Sign up to set email alerts
|

Saturation mutagenesis of a CepR binding site as a means to identify new quorum-regulated promoters in Burkholderia cenocepacia

Abstract: SummaryBurkholderia cenocepacia is an opportunistic pathogen of humans that encodes two genes that resemble the acylhomoserine lactone synthase gene luxI of Vibrio fischeri and three genes that resemble the acylhomoserine lactone receptor gene luxR. Of these, CepI synthesizes octanoylhomoserine lactone (OHL), while CepR is an OHL-dependent transcription factor. In the current study we developed a strategy to identify genes that are directly regulated by CepR. We systematically altered a CepR binding site (cep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…A recent study has reported a different consensus sequence in B. cenocepacia K56‐2, as well as the experimental demonstration of the direct regulation for two genes, BCAL0510 and BCAM1869 (Wei et al. ). BCAM1869 is an ortholog of Bamb_4117, which is located between cepR and cepI , and for which we have predicted a putative cep box (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A recent study has reported a different consensus sequence in B. cenocepacia K56‐2, as well as the experimental demonstration of the direct regulation for two genes, BCAL0510 and BCAM1869 (Wei et al. ). BCAM1869 is an ortholog of Bamb_4117, which is located between cepR and cepI , and for which we have predicted a putative cep box (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…This approach does not allow to discriminate genes directly or indirectly controlled by QS (Wei et al. ). To partially circumvent this shortcoming, we have performed a bioinformatics search for the presence of putative cep boxes upstream of transcriptional units identified in the screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic organization of the B. cenocepacia bcam1869 locus. The bcam1869, cepI, and bcam1871 genes are transcriptionally induced by CepR-OHL complexes [25]. B).…”
Section: Figmentioning
confidence: 99%
“…Typically, quorum-sensing systems operate as transcription networks regulated by a LuxR-type transcription regulator and its cognate AHL (reviewed in reference 3). While many studies on quorum sensing have focused on extending the known regulon (4)(5)(6)(7)(8)(9)(10)(11)(12)(13), few have considered the temporary aspects of transcription regulation (12). Interestingly, studies on regulatory networks are revealing the dynamic behavior and precision timing of transcription control (14,15).…”
mentioning
confidence: 99%